2006
DOI: 10.1097/01.rhu.0000222053.47708.dd
|View full text |Cite
|
Sign up to set email alerts
|

Nephrogenic Fibrosing Dermopathy/Nephrogenic Systemic Fibrosis in 2 Patients With End-Stage Renal Disease on Hemodialysis

Abstract: Nephrogenic fibrosing dermopathy/nephrogenic systemic fibrosis (NFD/NSF) is a newly recognized disorder occurring in patients with renal failure. It is manifested by progressive cutaneous and systemic fibrosis involving the extremities and the trunk with usual sparing of the face and internal organs. NFD/NSF can lead to joint contractures and painful disability. The etiology is unknown and there are no proven effective treatments. NFD/NSF must be distinguished from other clinically similar disorders such as sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…This was demonstrable in both renal insufficiency and normal renal function. Multinucleated giant cells, similar to those observed in humans (Kim et al, 2006), were found in the dermis using this model. The morphology of the electron-dense deposits was similar to what has been described for gadolinium oxide in simulated phagolysosomal fluid in vitro (Li et al, 2014).…”
Section: Discussionsupporting
confidence: 85%
“…This was demonstrable in both renal insufficiency and normal renal function. Multinucleated giant cells, similar to those observed in humans (Kim et al, 2006), were found in the dermis using this model. The morphology of the electron-dense deposits was similar to what has been described for gadolinium oxide in simulated phagolysosomal fluid in vitro (Li et al, 2014).…”
Section: Discussionsupporting
confidence: 85%
“… 29 described a case report of four patients with features similar, but not identical to scleromyxoedema whereas a later follow‐up study in 2008 confirmed the diagnosis of NSF 30 . Thus, we believe that the participation of a skilled dermatologist or rheumatologist with specialist knowledge of scleroderma diseases is required in the determination of this disease to avoid diagnostic misclassification 31–33 …”
Section: Discussionmentioning
confidence: 97%
“…Often the cells are described as being spindle shaped (61,77), fibroblasts (6), fibroblast like (56), fibrohistiocytic (68,75,82), or "polygonal epitheliod fibroblasts" (6). With the use of light microscopy, the dermal collagen is notably increased (27), with bundles haphazardly arranged (56) or "disorganized" (48). Mucin may be present (29,55,61,105), but is not required for the diagnosis (59).…”
Section: Histology and Immunohistologymentioning
confidence: 99%